2011
DOI: 10.1186/ar3537
|View full text |Cite
|
Sign up to set email alerts
|

Abatacept with methotrexate versus other biologic agents in treatment of patients with active rheumatoid arthritis despite methotrexate: a network meta-analysis

Abstract: IntroductionThe goal of this study was to compare the efficacy in terms of Health Assessment Questionnaire change from baseline (HAQ CFB), 50% improvement in American College of Rheumatology criterion (ACR-50) and Disease Activity Score in 28 joints (DAS28) defined remission (< 2.6) between abatacept and other biologic disease modifying anti-rheumatic drugs (DMARDs) in patients with rheumatoid arthritis (RA) who have inadequate response to methotrexate (MTX-IR).MethodsA systematic literature review identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 37 publications
2
23
1
6
Order By: Relevance
“…Especially, in 29 bio-naïve patients, the remission rate was 37.9% (11/29 patients) at 52 weeks, compared with 14.3% in 7 bio-switch patients. A previous meta-analysis study that examined the effectiveness of abatacept combined with MTX against active RA, reported that the remission rate, defined by DAS28-ESR52.6, was 40.2% (95% confidence interval: 10.4-80.3%) [25]. Thus, the remission rate in our study seems to be comparable with that of previous studies on similar RA patients.…”
Section: Discussionsupporting
confidence: 80%
“…Especially, in 29 bio-naïve patients, the remission rate was 37.9% (11/29 patients) at 52 weeks, compared with 14.3% in 7 bio-switch patients. A previous meta-analysis study that examined the effectiveness of abatacept combined with MTX against active RA, reported that the remission rate, defined by DAS28-ESR52.6, was 40.2% (95% confidence interval: 10.4-80.3%) [25]. Thus, the remission rate in our study seems to be comparable with that of previous studies on similar RA patients.…”
Section: Discussionsupporting
confidence: 80%
“…Subsequently, the use of additional therapeutic agents targeting alternate cytokines, including IL-6 in RA, as well as IL-23 or IL-17 in the SpAs, represent additional "activation nodes" involving these cytokines [24][25][26][27][28][29] . Therapies targeting T cell co-stimulatory effector pathways also have been shown to be effective in controlling synovial inflammation and joint damage in RA 30 . More recently, therapies targeting B cells also have shown efficacy, providing evidence of the importance of both T and B cells in RA pathogenesis 31 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…RA is a complex area with many clinical factors potentially influencing the relative efficacy and safety of the individual bDMARDs (eg, treatment and response history, concomitant use of MTX, dosing of the administered bDMARD, and pretreatment disease duration) 8 10 11 15 16 18. Similarly, MTC is a relatively new statistical approach that has little established guidance on how to perform a gold-standard analysis 17.…”
Section: Introductionmentioning
confidence: 99%